Selected Cognitive Abilities in Elite Youth Soccer Players - Baláková, Veronika; Boschek, Petr; Skalíková, Lucie (Journal of human kinetics, 2015)
The identification of talent in soccer is critical to various programs. Although many research findings have been presented, there have been only a few attempts to assess their validity. The aim of this study was to determine the relationship between talent and achievement variables in the Vienna Test System. The participants were 91 Czech soccer players, representing four youth soccer teams, who were born in the year 2000. These boys were divided into two groups according to their coaches' assessments using a TALENT questionnaire. A two-factor model (component 1: "kinetic finesse"; component 2: "mental strength") was designed to interpret the responses of the coaches on the questionnaire. The Vienna Test System was used to determine the level of players' cognitive abilities. In total, the subjects performed seven tests in the following order: Raven's Standard Progressive Matrices (SPM), a reaction test (RT), a determination test (DT), a visual pursuit test (LVT), a Corsi Block-Tapping Test (CORSI), a time/movement anticipation test (ZBA), and a peripheral perception test (PP). To analyze the relationship between talent and achievement variables within the Vienna Test System, correlation analyses were performed. The results revealed that the talented group attained significantly better results on only 1 of the 16 variables, which was ZBA2: movement anticipation - deviation of movement median (r = .217, p = .019). A comparison of the two talent components showed that component 1 ("kinetic finesse") was a more significant factor than component 2 ("mental strength"). Although we observed statistically significant correlations, their actual significance remains questionable; thus, further research is required.